Drug-based pain management in people with dementia after hip or pelvic fractures: a systematic review protocol. Issue 1 (December 2016) - Kuske, S.; Moschinski, K.; Andrich, S.; Stephan, A.; Gnass, I.; Sirsch, E.; Icks, A.
Abstract Background Studies show that people with dementia do not receive the same amount of analgesia after a hip or pelvic fracture compared to those without cognitive impairment. However, there is no systematic review that shows to what extent and how drug-based pain management is performed for people with dementia following a hip or pelvic fracture. The aim of this systematic review is to identify studies addressing drug-based pain management for people with dementia who have had a hip or pelvic fracture for which they had either an operation or conservative treatment. We will analyse to what extent and how the drug-based pain treatment for people with dementia is performed across all settings and how it is assessed in the studies. Methods The development of this systematic review protocol was guided by the PRISMA-P requirements, which will be taken into consideration during the review procedure. MEDLINE, EMBASE, CINAHL, Web of Knowledge and ScienceDirect will be searched, using keywords such as "analgesia", "dementia", "cognitive impairment", "pain treatment", "hip fracture" or "pelvic fracture". Publications published up to January 2016 will be included. The data extraction and a content analysis will be carried out systematically, followed by a critical appraisal. Discussion This review will provide a valuable overview on the current evidence on drug-based pain management for PwD in all settings who were conservatively treated after a hip or pelvic fracture. The review may expose a need to enhance pain management for PwD. It may also provide motivation for healthcare providers and policymakers to give this topic their attention and to facilitate further research by considering aspects of care transitions in all settings. Systematic review registration PROSPEROCRD42016037309